2017
DOI: 10.1186/s13012-017-0582-z
|View full text |Cite
|
Sign up to set email alerts
|

Adapting an adherence support workers intervention: engaging traditional healers as adherence partners for persons enrolled in HIV care and treatment in rural Mozambique

Abstract: BackgroundSystematic adaptation of evidence-informed interventions that increase retention in care and improve adherence to antiretroviral therapy (ART) are essential to ending the HIV epidemic in rural sub-Saharan Africa. We selected and adapted an adherence support worker intervention employed in Malawi for use by traditional healers in rural Mozambique. Given the levels of trust and dependence previously expressed by persons living with HIV (PLHIV) for traditional medicine, we adapted the program to engage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 65 publications
(49 reference statements)
2
45
0
5
Order By: Relevance
“…Healers were trained in identifying factors to bring to the attention of a health care provider and health care providers at the clinic were included throughout the creation of the program to increase acceptability towards the intervention. 42 Despite these efforts, sociocultural norms, including dismissive attitudes towards healers from health care providers, made advocacy di cult. Patients' interviews highlighted the challenges they encountered with disrespectful health care providers and poorly implemented clinical services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Healers were trained in identifying factors to bring to the attention of a health care provider and health care providers at the clinic were included throughout the creation of the program to increase acceptability towards the intervention. 42 Despite these efforts, sociocultural norms, including dismissive attitudes towards healers from health care providers, made advocacy di cult. Patients' interviews highlighted the challenges they encountered with disrespectful health care providers and poorly implemented clinical services.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence-based intervention was originally designed for use by community health workers. The program was tailored for use by traditional healers using the ADAPT-ITT framework 54 in 2017, 43 and to allow for patients to select the healer of their choice. Traditional healers who were selected for the program were given two weeks of counseling and clinical training, six hours of contact time with local health care providers to facilitate relationship building, and a structural change at the health system that allowed healers to "jump the queue" with their patients.…”
Section: Created Inmentioning
confidence: 99%
See 1 more Smart Citation
“…21 La formation des TPS avec une procédure intégrée a déjà été recommandée par d’autres auteurs 22 : (1) les TPS collaborent avec les services de santé modernes, (2) des structures locales sont créées pour faciliter l’accès aux services de santé, (3) les TPS participent à des études et des recherches avec les professionnels de santé 23 , (4) le succès de cette démarche dépend d’une bonne identification des TPS avec connaissance et disponibilité, ainsi que de l’établissement d’une relation solide avec les professionnels, en manifestant de l’intérêt, du respect professionnel, et de la confiance; il faudra aussi assurer la garantie d’un prix juste en échange de leur temps et de leurs plantes, ainsi que les droits de propriété intellectuelle personnels et collectifs. 24 , 25 , 26 …”
Section: Discussionunclassified
“…While some studies have indicated that THPs lack the biomedical skills and knowledge to diagnose and treat HIV [34,35,44], THPs who are trained in HIV/AIDS have been used to educate patients about the causes and consequences of HIV, and have provided physical and psychosocial community-based HIV care [19,45–47]. A quantitative study conducted among patients consulting THPs in the context of HIV/AIDS found that PLHIV did so owing to several complex health situations [28].…”
Section: Introductionmentioning
confidence: 99%